2012
DOI: 10.1080/01496395.2011.620582
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Lactic Acid through Polymer Inclusion Membranes Containing Ionic Liquids

Abstract: Optically pure lactic acid that can be prepared by fermentation is one of the important raw materials for biodegradable polymer. Since an economical technique is desired that separates lactic acid from the fermentation broth, we proposed lactate permeation through a poly(vinyl chloride)(PVC)-based membrane containing ionic liquids as a carrier. Lactate was successfully permeated through polymer inclusion membranes (PIMs) containing Aliquat 336, Cyphos IL -101, and -102 as ionic liquids. From the viewpoints of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…However, the main disadvantage of this method is the use of large volumes of organic solvents and the active compounds, which are often toxic for microorganisms applied in the fermentation processes (15,16). Another possibility which has been recently developed is a method using polymer inclusion membranes (17)(18)(19)(20)(21)(22). Such a solution can allow not only for the reduction of the quantity of harmful by-products, but also reduce the amount of the substance used as carriers in the PIM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main disadvantage of this method is the use of large volumes of organic solvents and the active compounds, which are often toxic for microorganisms applied in the fermentation processes (15,16). Another possibility which has been recently developed is a method using polymer inclusion membranes (17)(18)(19)(20)(21)(22). Such a solution can allow not only for the reduction of the quantity of harmful by-products, but also reduce the amount of the substance used as carriers in the PIM.…”
Section: Introductionmentioning
confidence: 99%
“…A PIM including ILs has a similar coniguration to SILM, and it is considered to be a kind of SILM. It is found that the PIM including ILs became more stable than conventional SILM [22].…”
Section: Polymer Inclusion Membranementioning
confidence: 92%
“…PILIMs are obtaining by mixing the relatively inert polymeric supports with ionic liquids. Recently, it has been demonstrated the higher stability of PILIMs compared with SILMS against high polar medium [42] and PILIMs have been applied to different fields such us separation of organic compounds [43], metal ions [44] and in ions selective electrodes [45].…”
Section: Introductionmentioning
confidence: 99%